Aktivitas Mikrobiologis Endofit dari Ekstrak Daun Binahong (Anredera cordifolia (Ten.) Steenis) - Jendri Mamangkey; Lukas Pardosi; Riska Septia Wahyuningtyas (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Endophytic bacteria and fungi inhibite the tisues of living plant. Both of them are significant components of plant microecosystems. Current research was performed to explain several microbiological activities (production of extracellular enzymes, antioxidants, and antibacterials) of endophytic bacteria and fungi from binahong leaves extract (Anredera cordifolia (Ten.) Steenis). In this case, the research was conducted by applying a review of several literature reviews published online on Google Scholar and several journals listed on the ScienceDirect site. Based on the results obtained from the research reports from several scientific journal sources, there are four types of extracellular enzymes produced by the endophytic bacteria of the Anredera cordifolia plant, including proteinase, amylase, esterase, and cellulase. In addition, the endophytic bacteria of Pseudomonas aeruginosa from the leaves extract of Anredera cordifolia has antioxidant activity, which is volatile compounds including cis-9-Octadecenoic acid, 2-dodecenoic acid, and 9 octadecenamide produced by endophytic bacteria of Pseudomonas sp. Furthermore, the endophytic bacteria isolated from Anredera cordifolia leaves extract inhibits the growth of E. coli ATCC 35216 and S. aureus ATCC 29523. Meanwhile, the endophytic fungi from Anredera cordifolia leaves extract inhibite the growth of E.coli and S. aureus bacteria. Therefore, understanding the relationship between bacteria and endophytic fungi from the leaves extract of binahong (Anredera cordifolia (Ten.) Steenis) is essential. This knowledge can be utilized and applied well for the future production of higher quality and more medicinal plants from binahong plant (Anredera cordifolia (Ten.) Steenis).